Characterization and Validation of Arg286 Residue of IL-1RAcP as a Potential Drug Target for Osteoarthritis - Dailing, Angela; Mitchell, Kelsey; Vuong, Ngoc; Lee, Kyung Hyeon; Joshi, Reva; Espina, Virginia; Haymond Still, Amanda; Gottschalk, Carter J.; Brown, Anne M.; Paige, Mikell; Liotta, Lance A.; Luchini, Alessandra (Frontiers in Chemistry, 2021)
Osteoarthritis (OA) is the most common form of arthritis and the fastest growing cause of chronic disability in the world. Formation of the ternary IL-1β /IL-1R1/IL-1RAcP protein complex and its downstream signaling has been implicated in osteoarthritis pathology. Current OA therapeutic approaches target either the cytokine IL-1β or the primary receptor IL-1RI but do not exploit the potential of the secondary receptor IL-1RAcP. Our previous work implicated the Arg286 residue of IL-1RAcP as a key mediator of complex formation. Molecular modeling confirmed Arg286 as a high-energy mediator of the ternary IL-1β complex architecture and interaction network. Anti-IL-1RAcP monoclonal antibodies (mAb) targeting the Arg286 residue were created and were shown to effectively reduce the influx of inflammatory cells to damaged joints in a mouse model of osteoarthritis. Inhibitory peptides based on the native sequence of IL-1RAcP were prepared and examined for efficacy at disrupting the complex formation. The most potent peptide inhibitor had an IC50 value of 304 pM in a pull-down model of complex formation, and reduced IL-1β signaling in a cell model by 90% at 2 μM. Overall, therapies that target the Arg286 region surface of IL-1RAcP, and disrupt subsequent interactions with subunits, have the potential to serve as next generation treatments for osteoarthritis.